2020
DOI: 10.1186/s12964-020-00629-3
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-4/PAR-3 signaling regulates focal adhesion dynamics in mesenchymal cells

Abstract: Background: Syndecans regulate cell migration thus having key roles in scarring and wound healing processes. Our previous results have shown that Thy-1/CD90 can engage both αvβ3 integrin and Syndecan-4 expressed on the surface of astrocytes to induce cell migration. Despite a well-described role of Syndecan-4 during cell movement, information is scarce regarding specific Syndecan-4 partners involved in Thy-1/CD90-stimulated cell migration. Methods: Mass spectrometry (MS) analysis of complexes precipitated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 73 publications
1
23
1
Order By: Relevance
“…93,95,[97][98][99] Future experimentation would be needed to characterize the kinetics of expression of adhesive proteins, focal adhesion turnover, and intracellular signaling in order to elucidate the relative roles of integrins and syndecans in mediating degenerative NP cells interactions with the extracellular environment. 86,93,95,[99][100][101] While the dual presentation of integrin-binding and syndecan-binding peptides did not elicit a synergistic response in the present study, combinations of other peptides may have the beneficial effects not specifically observed here. 102 For example, combining IKVAV and GD-6 which each promoted the greatest expression of different phenotypic markers may result in an additive or synergistic effect and warrants future study.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…93,95,[97][98][99] Future experimentation would be needed to characterize the kinetics of expression of adhesive proteins, focal adhesion turnover, and intracellular signaling in order to elucidate the relative roles of integrins and syndecans in mediating degenerative NP cells interactions with the extracellular environment. 86,93,95,[99][100][101] While the dual presentation of integrin-binding and syndecan-binding peptides did not elicit a synergistic response in the present study, combinations of other peptides may have the beneficial effects not specifically observed here. 102 For example, combining IKVAV and GD-6 which each promoted the greatest expression of different phenotypic markers may result in an additive or synergistic effect and warrants future study.…”
Section: Discussioncontrasting
confidence: 61%
“…93,95,9799 Future experimentation would be needed to characterize the kinetics of expression of adhesive proteins, focal adhesion turnover, and intracellular signaling in order to elucidate the relative roles of integrins and syndecans in mediating degenerative NP cells interactions with the extracellular environment. 86,93,95,99101…”
Section: Discussionmentioning
confidence: 99%
“…33 In addition, a recent study demonstrated that the binding of syndecan-4 to PAR-3, involve the Thy-1/CD90-induced FA dynamics in mesenchymal cells by regulating FAK autophosphorylation and Tiam1 activation. 49 While our study demonstrates a clear regulatory impact of both syndecan-4 and miR-140-3p on ECMrelated regulators and mediators of cancer cell adhesion and motility, this regulation partially occurred in a context and cell-type-dependent manner. We ascribe this to the pleiotropic nature of both syndecan and miRNA functions: syndecan-4 acts as a multifunctional coreceptor that impacts on numerous signaling pathways.…”
Section: Discussionmentioning
confidence: 56%
“…FA turnover is an important event during directional cell migration. Moreover, Thy-1 has been shown to directly interact with integrins and syndecan 4 to form a trimolecular complex that facilitates initial cell adhesion by enhancing FA formation and subsequently, promoting migration by regulating contractility and FA turnover (Avalos et al, 2004;Hermosilla et al, 2008;Avalos et al, 2009;Kong et al, 2013;Fiore et al, 2014;Fiore et al, 2015;Lagos-Cabre et al, 2017;Burgos-Bravo et al, 2020;Valdivia et al, 2020). Although the bidirectional signaling pathways triggered by Thy-1/integrin/ syndecan 4 clustering and activation remain unexplored during skin injury, the biological significance of each of these molecules by themselves has been proven important for an efficient wound healing process.…”
Section: Thy-1 Integrins and Syndecan 4 Are Cell-cell And Cell-matrix...mentioning
confidence: 99%
“…Interestingly, Thy-1-mediated migration and focal adhesion dynamics in embryonic fibroblasts depend on the recruitment of Partitioning-defective 3 (PAR3) to the cytoplasmic tail of syndecan 4. Consequently, PAR3 silencing inhibits FA disassembly triggered by Thy-1 stimulation, favoring fibroblast adhesion instead of migration (Valdivia et al, 2020). Further research is necessary to determine if the Thy-1/syndecan 4 interaction can also modulate fibroblast proliferation, differentiation, or ECM secretion.…”
Section: Proliferative Phasementioning
confidence: 99%